Effect of Endoscopic Sinus Surgery on Eustachian Tube Dysfunction in Chronic Rhinosinusitis - Yaseen, Imran; Hakim, Abdul; Malik, Kamran Zamurrad; Shah, Ausaf Ahmad; Manzoor, Faisal; Hanif, Shahzad (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess the effectiveness of endoscopic sinus surgery (ESS) on symptoms of Eustachian Tube Dysfunction (ETD) in adult patients with chronic rhinosinusitis (CRS).Study Design: Quasi-experimental studyPlace and Duration of Study: Department of ENT, Combined Military Hospital, Rawalpindi, Pakistan, from Dec to Jan 2022.Methodology: The effect of ESS on ETD of 82 patients was evaluated by analyzing retrospective data from the Sino-Nasal Outcome Test (SNOT-22) and Eustachian Tube Dysfunction Questionnaire 7 (ETDQ-7) assessments in adult CRS patients who underwent ESS.Results: The median (IQR) ETDQ-7 score was 16.0(5), with 50 patients demonstrating clinically significant ETD indications with an ETD-Q score of 15.0 and above. On the other hand, the median (IQR) SNOT-22 score was 45.0(14). The Spearman’s correlation coefficient value of 0.24 (p=0.031) indicated a significant relationship between ETDQ-7 and the total SNOT-22 score.Conclusion: These results suggest that the E-tube performance of adult CRS patients improves considerably after ESS, and it should be implemented for the management of CRS in adult patients with Eustachian tube dysfunction.